The Role of Islamic Family Law in Protecting Women and Children in the Context of the Pandemic: Case Studies in Developing Countries - Lutfia, Lubna; B, Fowler (Journal of Islamic Family Law, 2025)
The COVID-19 pandemic has posed various challenges for women and children, including increased cases of violence and difficulties in accessing legal services. Islamic family law plays a crucial role in protecting the rights of Muslims in this context. This study aims to analyze the role of Islamic family law in safeguarding women and children in developing countries during the pandemic, while examining the impact of parents' legal knowledge on their children's well-being. This research employs a qualitative method with a case study approach, involving semi-structured interviews and questionnaires distributed to 30-50 respondents, including women experiencing violence and legal activists. The findings indicate that approximately 70% of respondents are aware of their legal rights; however, many face barriers, including social stigma and complex legal procedures. Additionally, children from families with higher legal knowledge exhibit better well-being compared to those from families with lower legal knowledge. This study recommends better legal education and reforms in the legal system to enhance protections for women and children.